PENGARUH PENGALAMAN KONSUMEN, KUALITAS LAYANAN, DAN PERSEPSI NILAI TERDAHAP NIAT PEMBELIAN KEMBALI KONSUMEN SHOPEE DI DAERAH ISTIMEWA YOGYAKARTA - Asser Trio Simanjuntak; Rudy Badrudin (LPPM STIE YKPN Yogyakarta, 2024)
This research aims to test and analyze the influence of consumer experience, service quality, and perceived value on repurchase intentions among Shopee application users. The sampling method used was purposive sampling, with data collection carried out through questionnaires filled out by 70 respondents. The research results show that the three hypotheses are supported and have a positive effect on repurchase intentions. The first hypothesis (H1) which states that consumer experience is positively related to repurchase intentions is supported by a beta value of 0.213 and a significance of 0.022, which is smaller than the standard 0.05. The second hypothesis (H2) which states that service quality is positively related to repurchase intentions is supported with a beta value of 0.538 and a significance of 0.000, indicating a very strong and significant relationship. The third hypothesis (H3) which states that perceived value is positively related to repurchase intention is supported by a beta value of 0.243 and a significance of 0.004, indicating a significant positive relationship between the variables tested.